The Impact of Refugee Crises on Host Labor Markets: The Case of the Syrian Refugee Crisis in Turkey - Yusuf Emre Akgündüz; Marcel van den Berg; Wolter Hassink (Institute for the Study of Labor (IZA), 2015)
The civil war in Syria has culminated into major refugee crises in its neighboring countries. By the end of 2013 more than half a million people were seeking shelter in cities and refugee camps in Turkey. We analyze how the Syrian refugee influx in Turkey has affected food and housing prices, employment rates and internal migration patterns in regions of Turkey where refugees are being accommodated. Refugee camps are geographically concentrated near the Syrian border, which enables us to employ the rest of regional Turkey as control group with a difference-in-difference approach to analyze the impact on local economies. Our findings suggest that housing and to a lesser degree food prices increased, but employment rates of natives in various skill groups are largely unaffected. Incumbent natives appear to be staying put considering the limited migration out of the region, but there is a significant decline in internal migration into regions hosting refugees. Nevertheless, the decline in internal in-migration is less than a tenth of the refugee influx, implying that there is little evidence of refugees crowding out natives in local labor markets.
Keywords: F22; J61; R23; 330; refugees; employment; migration; inflation; regional economy; difference-in-difference